Cytological DNA methylation for cervical cancer screening: a validation set - Kong, Linghua; Wang, Linhai; Wang, Ziyun; Xiao, Xiaoping; You, Yan; Wu, Huanwen; Wu, Ming; Liu, Pei; Li, Lei (Frontiers in Oncology, 2023)
LL and PL conceived of the original idea for the study, interpreted the results, performed the statistical analysis, edited the paper, and were the overall guarantors. LK, LW, ZW, XX, and LL obtained ethical approval, collected study samples, contributed to the preparation of the data set, interpreted the results, and contributed to drafting the paper. LW, ZW, and PL performed the DNA methylation analysis. YY and HW conducted the pathological evaluations. XX and MW contributed to the study design and interpretation of the results and commented on drafts of the paper. All of the authors have approved the final version of the manuscript.